Pengaruh Brand Image, Customer Satisfaction, Dan Sertifikasi Halal Terhadap Costumer Loyalty Pada Kosmetik Wardah (Pada Mahasiswi Fakultas Ekonomi dan Bisnis UNISMA) - Novanda Asalia; Nur Hidayati; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of Brand Image, Customer Satisfaktion, and Halal Certification on Customer Loyalty in Wardah Cosmetics (At Unisma Faculty of Economics and Business Students). This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study using the Slovin formula with the Snowball Sampling technique obtained 81 respondents.The results of this study indicate that partially there is a significant influence between Brand Image on Customer Loyalty, Customer Satisfaktion has a significant effect on Customer Loyalty, Halal certification has a significant effect on Customer Loyalty of Students of the Faculty of Economics and Business Unisma. Keywords: Brand Image, Customer Satisfaktion, Halal Certification and Customer Loyalty